2018
DOI: 10.1016/j.jqsrt.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

High accuracy line positions of the ν 1 fundamental band of 14 N 2 16 O

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Highlights  The  1 band of N 2 O is measured wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 42 publications
7
17
1
Order By: Relevance
“…A clear systematic discrepancy is visible, though remaining within the HITRAN frequency uncertainty of 3 MHz. Furthermore, this clear systematic tendency closely follows that reported in a recent work by AlSaif et al [21], using a combreferenced external-cavity QCL, shown by the red markers. Similar to that study, we fit a model based on the effective ro-vibrational Hamiltonian (see Eq.…”
Section: Line Positions Of the ν 1 Bandsupporting
confidence: 90%
See 3 more Smart Citations
“…A clear systematic discrepancy is visible, though remaining within the HITRAN frequency uncertainty of 3 MHz. Furthermore, this clear systematic tendency closely follows that reported in a recent work by AlSaif et al [21], using a combreferenced external-cavity QCL, shown by the red markers. Similar to that study, we fit a model based on the effective ro-vibrational Hamiltonian (see Eq.…”
Section: Line Positions Of the ν 1 Bandsupporting
confidence: 90%
“…We fit the vibrational term value G v , the rotational constant B v , and the quartic and sextic centrifugal distortion constants D v , H v of the vibrationally excited state (fixing L v to 0) and fixed the ground-state rotational and centrifugal distortion constants to those determined by Ting et al [39]. The fitted upper-state constants of the ν 1 band are presented in Table 2, and compared to those obtained by AlSaif et al [21]. Except for G v , the retrieved upper-state constants from our work and Ref.…”
Section: Line Positions Of the ν 1 Bandmentioning
confidence: 97%
See 2 more Smart Citations
“…The comparison between line centers obtained from repeated measurements of the same dip returns a statistical uncertainty of 4.5 kHz for the single measurement, which is consistent with a dip signal to noise ratio of about 200 and a sub-MHz dip. The retrieved line center frequency calculated as a weighted mean of the line positions obtained at different power values (38931326476.0(3.5) kHz) differs by 48 kHz from the calculations reported in [20,23], which are declared accurate to within 2.4 kHz, and by 57 kHz from a recent model based on Doppler broadened comb-calibrated spectra [24]. In a worst-case scenario, we estimate at the 50 kHz level the accuracy of our determinations, mainly limited by a residual few-percent asymmetry of the spectral baseline that emerges from the residuals (Fig.…”
Section: Methodscontrasting
confidence: 59%